Secure Authentication using Image Processing through Visual Cryptography (International Journal of Engineering and Computer Science, 2017)
Authentication is used by a server when the server needs to know exactly who is accessing their information or site. In this process, the user or computer has to prove its identity to the server or client. Usually, authentication by a server entails the use of a user name and password or through cards, retina scans, voice recognition, and fingerprints. An effective method for securely transmitting files, documents and images are found in the field of Visual Cryptography (VC). Visual cryptography method is a cryptographic technique which allows visual information (e.g. printed text, handwritten notes, and images etc.) to be encrypted in such a way that the decryption can be performed by the human visual system (HVS), without the aid of computers. This study focuses on securing a file or document through CAPTCHA images using image processing. The study is to be carried out in two phases where the Phase I would comprise Registration Phase and, Login Phase would be carried out in Phase II.